Investigating Prolonged Processes of Preparation, Review and Approval of Urban Comprehensive Plans, from Urban Planning and Architecture Authorities' Points of View, Using a Pragmatic Approach (between 2017–2022) - Seyyed Hossein Mirzadeh; Azam Afsharnia (صفه)
A range of criticisms have been put forward about urban master plans – the most important strategic documents for the planning and management of cities (or towns) – and their quality. The most important of these is about their prolonged processes of preparation, review, and approval as the main hinderance for efficiency and productivity. This pushes plans and programmes away from the realities at the time of approval, and makes them practically ineffective. In response, some urban planning experts are after fundamental changes in the process of preparation, review, and approval of master plans. This research focuses on finding reasons for prolonged processes, because without that all efforts to implement new approaches are doomed to fail, the experience of preparing urban structural-strategic plans in Iran being apoint in the case.To answer the main question of this research, urban planning managers of road and urban development in all provinces of Iran are selected to answer questionnairesdue to their seminal roles in the selection of consulting engineers, preparation, review, approval, communication, and even implementation of the urban master plans. Results show a variety of reasons for prolongation of the process, the most important of which being weaknesses, discordances, non-realisation of potentials, the lack of adequate training of experts, and the absence of experienced consulting engineers involving in preparation of master plans. The weakness of the experts and management bodies of institutions and groups causes problems such as the adoption of piecemeal approaches in master plans, or failures in fulfilling basic requirements for preparation of the plans such as acquiring updated aerial photographs, and as a result, it takes a long time bringingconsultation contracts to a conclusion.